Isolation and characterization of Burkholderia sp. strain CCA53 exhibiting ligninolytic potential - Akita, Hironaga; Kimura, Zen‑ichiro; Mohd Yusoff, Mohd Zulkhairi; Nakashima, Nobutaka; Hoshino, Tamotsu (SpringerOpen, 2016)
Microbial degradation of lignin releases fermentable sugars, effective utilization of which could support biofuel production from lignocellulosic biomass. In the present study, a lignin-degrading bacterium was isolated from leaf soil and identified as Burkholderia sp. based on 16S rRNA gene sequencing. This strain was named CCA53, and its lignin-degrading capability was assessed by observing its growth on medium containing alkali lignin or lignin-associated aromatic monomers as the sole carbon source. Alkali lignin and at least eight lignin-associated aromatic monomers supported growth of this strain, and the most effective utilization was observed for p-hydroxybenzene monomers. These findings indicate that Burkholderia sp. strain CCA53 has fragmentary activity for lignin degradation.